Accelerated Corneal Collagen Cross-Linking Using Topography-Guided UV-A Energy Emission: Preliminary Clinical and Morphological Outcomes. (28th November 2016) - Mazzotta, Cosimo; Moramarco, Antonio; Traversi, Claudio; Baiocchi, Stefano; Iovieno, Alfonso; Fontana, Luigi
Abstract : Purpose . To assess the clinical and morphological outcomes of topography-guided accelerated corneal cross-linking. Design . Retrospective case series. Methods . 21 eyes of 20 patients with progressive keratoconus were enrolled. All patients underwent accelerated cross-linking using an ultraviolet-A (UVA) exposure with an energy release varying from 7.2 J/cm 2 up to 15 J/cm 2, according to the topographic corneal curvature. Uncorrected (UDVA) and corrected (CDVA) distance visual acuity, topography, in vivo confocal microscopy (IVCM), and anterior segment optic coherence tomography (AS-OCT) were evaluated preoperatively and at the 1, 3, 6, and 12 months postoperatively. Results . 12 months after surgery UDVA and CDVA did not significantly vary from preoperative values. The average topographic astigmatism decreased from- 4.61 ± 0.74 diopters (D) to- 3.20 ± 0.81  D and coma aberration improved from 0.95 ± 0.03  μ m to 0.88 ± 0.04  μ m after surgery. AS-OCT and IVCM documented differential effects on the treated areas using different energies doses. The depths of demarcation line and keratocyte apoptosis were assessed. Conclusions . Preliminary results show correspondence between the energy dose applied and the microstructural stromal changes induced by the cross-linking at various depths in different areas of treated cornea. One year after surgery a significant reduction in the topographic astigmatism and comatic aberration was detected. None of the patients developed significant complications.